Penatalaksanaan Terapi Latihan Pada Post Operasi Fraktur Colles sinistra di rs. Ortopedi prof. Dr. R. Soeharso surakarta - Sari, Eka Nofita, Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Colles fracture is a fracture that often occurs in the elderly patients with falling position resting on the stretched hands so that a fracture happened on radius distal to dorsal. Formulation of the Problem: Can exercise therapy reduce the pain, the oedema, and increase the muscle strength and add LGS on colles sinistra fracture? Objective: To examine the effect of exercise therapy of active passive movement in the colles sinistra fracture case. Results: After doing four times treatment, the result showed reduction on some pains which are; the silent pain T1: 3,7cm T4: 1.5 cm, the pressure pain T1: 5,6cm T4: 3,2cm, the movement pain T1: 7,9cm T4: 5,4cm, the decrease of figure of eight oedema T1: 45cm T4: 44cm, the Proc. Styloideus central point 5cm, 10cm, 15cm and above T1: 17cm, 20cm, 21cm into T4: 16cm, 19cm, 21cm, the increase of flexor and extensor muscle strength T1: 3 into T4: 4, the increase of LGS joints Wrist active movement T1 (s) 10 ° -0 ° -20 °, (f) 5 ° -0 ° -10 ° T4 (s) 15 ° -0 ° -25 °, (f) 5 ° -0 ° -15 ° the the increase of LGS joints Wrist passive movement T1 (s ) 15 ° -0 ° -25 °, (f) 10 ° -0 ° -15 ° T4 (s) 20 ° -0 ° -30 °, (f) 10 ° -0 ° -20 °, the elbow joint active movement T1 (s) 5 ° -0 ° -80 ° T4 (s) 5 ° -0 ° -85 ° the elbow joint passive movement T1 (s) 5 ° -0 ° -90 ° T4 (s) 5 ° - 0 ° -95 °, the LGS of active fingers MCP of the 2nd finger until the 5th finger increased about 2-5 °, the PIP of the of the 1st finger until the 5th finger increase about 2-5 °, the DIP of the 1st finger until the 5th finger increased about 2-5 °, the passive movement of MCP of the 2nd finger until the 5th finger increased 5-8 °, the PIP of the 1st finger until the 5th finger increased 5-10 ° and the DIP of the 1st finger until the 5th finger increased 3-8 °. Conclusion: From the results above, it shows that there is a decrease of pain, an addition of LGS, a decrease of oedema, and an increase of muscle strength by using active passive movement exercise therapy.